Risk factors of postural defects in children at school age - Latalski, Michał; Bylina, Jerzy; Fatyga, Marek; Repko, Martin; Filipovic, Milan; Jarosz, Mirosław J; Borowicz, Kinga B; Matuszewski, Łukasz; Trzpis, Tadeusz (Annals of agricultural and environmental medicine, 2013)
INTRODUCTION AND OBJECTIVE: Postural defects increasingly more often concern children and adolescents at school age. The lack of prophylaxis and neglecting adequate procedures may lead to limitations of physical and motor abilities, back pain, or the development of severe spinal deformities. Recognition of the risk factors conducive to the occurrence of the disorder allows the creation of adequate conditions for the psychomotor development of children, as well as the elaboration and implementation of specified educational schemes directed at schools and parents. The study concerned determination of the risk factors for the development of postural defects in school age children. MATERIAL AND METHODS: The study was conducted by means of a diagnostic survey. The study group covered 380 children aged 14 (175 girls (46.1%) and 205 boys (53.9%))--selected at random from schools in eastern Poland and the Czech Republic. The significance of the relationships between variables was investigated by means of chi-square test for independence. The differences between the empirical and theoretical sample distribution was examined by means of chi-square goodness-of-fit test. The significance level was set at p=0.05. RESULTS: The BMI in the population examined was 20.2, on average (from 14-39). Respondents living in rural areas and small towns constituted 57.63% of the study group, while inhabitants of medium-size and large cities--42.37%. The majority of children in the study had been previously examined for the occurrence of postural defects (74.2%), whereas nearly every tenth child had never undergone such an examination. As many as 16.3% of adolescents did not know whether they had ever participated in a screening test. A defect was detected in 14.7% of children, in 56.6% no asymmetry was detected, while approximately 30% were not aware if their body posture was normal or not. CONCLUSIONS: 1. There is a relationship between physical activity of the child and the occurrence of postural defects. 2. There is a relationship between the economic standard of the family and awareness of own state of health. 3. There is a need for the creation of a system of education for parents and children concerning postural defects and risks resulting from these defects.
Keywords: rozdělení chí kvadrát; Scoliosis; Adolescent; prevalence; postura těla; Posture; index tělesné hmotnosti; Male; Chi-Square Distribution; lidé; Humans; Body Mass Index; pohybová aktivita; průzkumy a dotazníky; socioekonomické faktory; Polsko; Czech Republic; rizikové faktory; mužské pohlaví; Surveys and Questionnaires; Socioeconomic Factors; Prevalence; Česká republika; ženské pohlaví; mladiství; Poland; Motor Activity; Female; Risk Factors; skolióza